Summer Regional Pentad Heat Wave in Eastern China and Their Possible Causes - Yao, Jingxin; Sun, Xuguang; Tang, Jianping; Ji, Yaqin; Xu, Yiming; Yang, Xiu-Qun (Frontiers in Earth Science, 2020)
Identification and understanding of persistent regional heat wave are essential for adaption and alleviation of its severe effects on human health and ecological environment, particularly under the situation of rapid global warming. Based on Climate Prediction Center (CPC) global daily maximum temperature from 1979 to 2019, considering extreme, persistence and regionality of heat wave, summer regional pentad heat wave (RPHW) is defined by summer daily maximum temperature above 35 ℃ with no less than 3 days in a pentad, which is also required to cover more than 2% grids over the eastern China. It breaks down the continuity constraints in both time and space in previous regional heat wave definitions that mainly indicate the synoptic phenomena. Besides, our RPHW is much useful in examining climatic features of regional heat wave, since it filters out the weather noises to some extend in terms of a pentad window. Three categories of RPHW are identified by K-means cluster analysis over the eastern China, i.e., North-Central China (NCC), Central China (CC) and South China (SC). Generally, intensity and area of RPHW are positively proportional to each other, and more RPHW appears in SC but with weaker intensity, whereas less RPHW locates in NCC and CC with stronger intensity. While RPHW in CC and SC mostly appears in middle-late summer, RPHW in NCC mainly occurs in early-middle summer which is transferred from the middle-late summer before the late 1990s. Most RPHW persists for 1 pentad and occasionally for 5 or 6 pentads at most. And both frequency and accumulated days of RPHW have been significantly increased since the late 1990s, particularly in CC and SC. Significant high-pressure anomalies are accompanied with the RPHW in China, which favor more incoming net solar radiation, increasing surface soil temperature, and more upward surface longwave radiation and sensible heat flux as well, eventually forming the RPHW. Specifically, the RPHW in NCC and SC are mainly caused by diabatic heating from the land surface and adiabatic heating due to the anomalous subsidence movement, respectively; however, both the diabatic heating and the adiabatic heating are responsible for the RPHW in CC.